Precursors and Chemicals Frequently Used in the Illicit Manufacture of Narcotic Drugs and Psychotropic Substances 2017 - International Narcotics Control Board (United Nations, 2018)
Prepared by the Board, this annual report presents an analysis of the information at its disposal and, in appropriate cases, an account of the explanations, if any, given by or required of Parties, together with any observations and recommendations which The Board desires to make. This report is submitted to the Economic and Social Council through the Commission, which may make such comments as it sees fit.